Assessment of Serum Vitamin D in Patients with Bronchial Asthma - Hisham E. Abd El Aaty; Aml A. Abd El Aziz; Mahmoud M. El Habashy; Manal A. Saafan; Seham A. Abd El hamed (Egyptian Journal of Chest Disease and Tuberculosis, 2015)
Background: Asthma is one of the most common chronic diseases worldwide and has been increasing in prevalence over the last few decades; its exact cause remains unknown and likely has its origin in complex interactions among multiple genetic and environmental factors. The World Health Organization (WHO) stated that approximately 300 million people have asthma. Recently the effects of vitamin D as a hormone have gained attention. Vitamin D appears to have regulatory effects on every part of the immune system, vitamin D deficiency being linked to an array of immunologically based diseases focusing on asthma. So the assessment of serum vitamin D in patients with bronchial asthma is useful. Objective: The aim of this study is to assess the level of serum vitamin D in patients with bronchial asthma. Methods: The present study, included 50 subjects, 40 patients diagnosed as bronchial asthma and 10 healthy volunteers. The asthmatic patient group was divided into group (A) asthma in between attack and group (B) exacerbated asthma, that was divided into subgroups (I), (II) and (III) mild, moderate and severe exacerbated asthma, respectively according to severity of symptoms and FEV1. Results: Serum vitamin D level was highly significantly lower in the asthmatic patient group compared to the control subject group and lowest serum 25 hydroxy(OH) vitamin D value in the severely exacerbated asthma group. There was a positive correlation between decreased serum 25 (OH)D levels and decreased FEV1. Conclusions: Vitamin D deficiency was highly prevalent in asthmatic patients, there was a strong correlation between asthma severity and 25(OH) vitamin D concentrations and there was a direct and a positive significant correlation between vitamin D levels and pulmonary function tests in asthmatic patients, so the measurement of serum vitamin D levels in patients with bronchial asthma is very useful.